Parenting by men who batter: new directions for assessment and intervention - Edleson, Jeffrey L. (Interpersonal violence, 2007)
Introduction : involving men who batter in their children's lives / Jeffrey L. Edleson and Oliver J. Williams -- Shared parenting after abuse : battered mothers' perspectives on parenting after dissolution of a relationship / Carolyn Y. Tubbs and Oliver J. Williams -- Assessing the best interests of the child : visitation and custody in cases of domestic violence / Peter G. Jaffe and Claire V. Crooks -- Deciding on fathers' involvement in their children's treatment after domestic violence / Betsy McAlister Groves, Patricia Van Horn, and Alicia F. Lieberman -- A conceptual framework for intervening in the parenting of men who batter / Einat Peled and Guy Perel -- Guidelines for intervention with abusive fathers / Katreena L. Scott, Karen J. Francis, Claire V. Crooks, Michelle Paddon, and David A. Wolfe -- Working with fathers in batterer intervention programs : lessons from the Fathering after Violence project / Juan Carlos Arean and Lonna Davis -- Latino fathers in recovery / Ricardo Carrillo, Jerry Tello -- Evaluating parenting programs for men who batter : current considerations and controversies / Cris M. Sullivan